Edx participants’ profile: analysis of the factors that lead to the search for certification - Lins Rodrigues, Rodrigo (RENOTE, 2019)
Massive Online Open Courses (MOOCs) are freely accessible online courses with open registration. This term was first coined in 2008 when professors of University of Manitoba (Canada) started an online course free and open to anyone. In 2012, two platforms were launched, EdX and Coursera. Until now, these two platforms remain as the most popular MOOCs providers in the world attracting universities from all of the continents. The present study performs data analysis of Harvard and MIT courses available in EdX during the first four years of operation. The objective was to understand students’ and courses’ profiles and the factors that make certifications more attractive to the participants. This paper could identify some factors that contribute to students’ motivation in obtaining formal certification. It was important to see that variables related to engagement impact in the inclination to obtain a certification. Furthermore, demographical characteristics as sex and age are relevant so that institutions can focus on specific targets.